Echoes of Batingaw: Cultural and Historical Conservation in the City of Cabuyao - Andrada, Rostum O. (International Journal on Integrated Education, 2025)
In an era of globalization and digital distraction, local cultural identities are increasingly at risk of fading. This study focuses on Cabuyao City, Laguna, where the youth—often viewed as custodians of heritage—are showing signs of disconnection from their cultural and historical roots. It investigates the awareness levels of young residents and explores the lived experiences of local government officials (LGUs) involved in heritage preservation, addressing the urgent question: how can a community safeguard its heritage before it’s forgotten? Using a mixed-methods approach, the research combined a quantitative survey of 268 randomly selected youth (ages 18–30) with qualitative interviews involving three LGU officials in cultural affairs, tourism, and youth development. Quantitative data assessed youth awareness of cultural and historical elements, while thematic analysis of interviews revealed institutional insights. Findings point to a troubling lack of awareness among youth, particularly regarding the Sakdalista movement, though some familiarity exists with symbols like the Batingaw (Golden Bell). LGU officials cited challenges including digital distractions, lack of local history in education, and resource constraints. They emphasized the need for stronger community engagement, educational reform, and accessible digital tools. The study concludes that safeguarding Cabuyao’s heritage requires collaborative efforts between youth, schools, and LGUs. Recommendations include integrating local history into curricula, creating interactive digital resources, and launching community-driven heritage initiatives. These findings offer valuable direction for policymakers and practitioners aiming to strengthen cultural preservation, especially in developing regions facing similar pressures.